(untitled) - Maxwell, Steven (New York, 2000)
Linux is quickly becoming the operating system of choice, not only on desktops, but also for managing large-scale corporate networks. For system administrators working in a multi-platform environment hands-on guide to system configuration and server management.
Keywords: Mạng máy tính,Computer networks; Quản trị,Management